Integrating Nanomechanical Property Testing into a Correlative Imaging Workflow - RACHEL BOARD (2023)
This work is aimed at creating a cohesive workflow between correlative imaging techniques and nanomechanical property testing for materials analysis. There exist multiple features of a material, on varying length scales, that can determine its performance in its desired function. As technology advances new materials are developed to address new problems with more and more taking their inspiration from nature. The use of different techniques individually has been able to shed light on either the structure, property, or function of the materials, either manufactured or biological. Understanding has developed that the three aspects; structure, property, and function are related and should be considered together when analysing a material. Combining multiple techniques in a workflow will allow for revealing the ‘whole picture’ of the material. The methods of materials analysis used in this research are X-ray micro-CT, scanning electron microscopy (SEM), light microscopy, X-ray fluorescence (XRF), and nanoindentation. Each of the methods used here requires specific preparation methods prior to testing and one testing method may make the sample unsuitable for another testing method. Therefore, planning the sequence of testing before commencing is of high importance. Putting into place a workflow will not only reduce the likelihood of inhibiting further testing procedures but also reduce the time taken for completing a comprehensive analysis. The workflow proposed here takes into consideration what information can be gained as well as preparation techniques. Initially, this thesis will discuss correlative imaging detailing, sample preparation, and the capabilities of these techniques in uncovering the internal nano – to the macro-structure of antler bone and barnacle plate organisation, as well as the chemical uniformity of the inorganic phase of antler bone across the cross-section and the elongated crystallographic structures unique to the barnacle ala. Secondly, XRF will be explored for its role in the chemical analysis of biological materials and where this technique can be placed into the workflow to impact the overall understanding of the chemical composition in this instance in the application of antlers. Finally covered will be nanomechanical property testing for both stand-alone equipment and in-situ indentation. The suggested position for this technique in the workflow will be explained as it is used as the final connecting piece in determining the structure-function-property relationship of the material due to how the previous methods have directed the research process. Correlating the accelerated property mapping technique to the crystallographic structures in barnacle plates showed a reduced hardness in the elongated crystal region. Nanoindentation of the antler bone showed differences in modulus between the transverse and cross-sections as well as a reduction in average hardness between the male antler and the female reindeer that had calves and those that did not. Each of the individual pieces of information in this workflow when brought together unveils the hidden structure-property-function relationship in materials to provide an in-depth understanding.